Independence Hall - Smith, Roland 1951- (Sleeping Bear Press, 2008)
Thirteen-year-old Q and fifteen-year-old Angela expect their lives to become complicated when his mother and her father, wildly popular musicians, marry, but not that they will face spies and terrorists in Philadelphia, Pennsylvania
Keywords: Spies; Terrorism; Brothers and sisters; Musicians; Remarriage; Secret service -- Juvenile fiction; Detective and mystery stories; Brothers and sisters -- Juvenile fiction; Mothers -- Juvenile fiction; Philadelphia (Pa.); Philadelphia (Pa.) -- Juvenile fiction; Jugendbuch